2019
DOI: 10.3389/fimmu.2019.01263
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells in the Human Lungs

Abstract: The lung offers one of the largest exchange surfaces of the individual with the elements of the environment. As a place of important interactions between self and non-self, the lung is richly endowed in various immune cells. As such, lung natural killer (NK) cells play major effector and immunoregulatory roles to ensure self-integrity. A better understanding of their abilities in health and diseases has been made possible over the past decade thanks to tremendous discoveries in humans and animals. By precisely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 60 publications
2
63
0
Order By: Relevance
“…In other tumours where pTA-NKs have been investigated, CD9 is present on the cell surface of a subset of circulating CD56 bright CD16 -/low ; dNK-like cells are present in pNK of melanoma [62][63][64], lung [12,28,65] and colorectal cancers [25,66].Based on our evidence we confirmed that, even when it is difficult to detect tumour infiltrating NK, peripheral blood NK cells offer and indirect tool monitor the state of cancer patients according to their polarization.…”
Section: Discussionsupporting
confidence: 78%
“…In other tumours where pTA-NKs have been investigated, CD9 is present on the cell surface of a subset of circulating CD56 bright CD16 -/low ; dNK-like cells are present in pNK of melanoma [62][63][64], lung [12,28,65] and colorectal cancers [25,66].Based on our evidence we confirmed that, even when it is difficult to detect tumour infiltrating NK, peripheral blood NK cells offer and indirect tool monitor the state of cancer patients according to their polarization.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, Marquardt et al have identified a new adaptive-like KIR+/NKG2C+ NK cell subset with a CD49a+/CD56bright/CD16−trNK cell phenotype in human lung and in peripheral blood of HCMV-seropositive individuals, mentioned above (Marquardt et al, 2019). The adaptive-like lung trNK cells have been thus found to be hyper-responsive towards target cells (Hervier et al, 2019). This novel subset of human lung NK cells contributes to unique defense mechanisms in the context of the respiratory infection at this site (Cong and Wei, 2019).…”
Section: Memory-like Nk Cells Expansion In Various Pathological Condimentioning
confidence: 99%
“…Lung NK cells have recently been extensively reviewed in this journal (23,24), so that a summary of their most important features might be sufficient. Lungs are constantly exposed to microparticles from the environment.…”
Section: Nk Cells In the Lungsmentioning
confidence: 99%
“…Particularly, as the mucosal lung epithelium is at the interface between the outside world and the organism, it can become the entry site for infectious pathogens, be they bacterial, fungal, or viral in nature. Therefore, an extensive and sophisticated local immune response is waiting to be triggered at this anatomic location, and human NK cells, which represent around 5-20% of lung lymphocytes (24), are a part of it. The work of Marquardt et al has established that most human lung NK cells represented the circulating subset and had the mature CD56 dim CD16 bright phenotype (25).…”
Section: Nk Cells In the Lungsmentioning
confidence: 99%